Filogenia morfológica de Hypsiboas (Wagler, 1830) (HYLIDAE: HYLINAE: COPHOMANTINI) com ênfase nos grupos de H. albopunctatus e H. semilineatus sensu Faivovich et al. (2005) - Paulo Duraes Pereira Pinheiro (2013)
The Hypsiboas genus was removed from the synonymy of Hyla based on molecular studies, to group part of neotropical hylid species that possess the prepollex developed into a spine. Nowadays, it contains 84 described species, distributed into seven groups based on morphological or molecular affinities. However, morphological synapomorphies for the genus and its groups are unknown. In order to enhance the knowledge of phylogenetic relationships between groups and species of the genus, and test the monophyly and relationships of H. albopunctatus and H. semilineatus groups, a phylogenetic matrix of 53 terminals and 116 morphological characters was elaborated. Three more parsimonious trees with 887 steps were found. The only differences are restricted to part of H. pulchellus group. Despite the low support of the clades, the H. albopunctatus (excepting H. heilprini), H. punctatus, and H. pulchellus groups remain monophyletic. The H. faber group remain related to H. pulchellus group, but it is paraphyletic. H. boans and H. wavrini are related to H. faber group, and the other species of H. semilineatus group form a clade sister to H. albopunctatus group. The H. albopunctatus group has four non-exclusive synapomorphies: posterior lips of tadpoles with three rows of keratodonts; inner wall of spiracle of tadpole with 2/3 of distal end free; loreal strip present on adults; and hyoid plate medially mineralized in adults. The H. semilineatus group has five non-exclusive synapomorphies: nuptial excrescences present on males; white stripe on lower lip present on adults; reticulated palpebral membrane; absence of contact between m. submentalis and m. intermandibularis; and lateral process of VIII vertebra oriented orthogonally to the body axis.